An orally bioavailable BRD4 inhibitor disrupts expansion of a pathogenic epithelial-mesenchymal niche in bleomycin-induced fibrosis - Melissa Skibba; Zonghui Ma; Carole L. Wilson; Zhiqing Liu; Haiying Chen; Bing Tian; Thomas J. Harr; Lynn M Schnapp; Nathan Sandbo; Jia Zhou; Allan R. Brasier (Respiratory Research)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a relentlessly progressive and fatal disease with few effective therapies available. Fibrosis is driven, in part, by cell-state transitions of epithelial progenitors within the airways that repopulate the injured alveoli. This alveolar atypia affects gas exchange and stimulates ECM production. We sought to examine the role of BRD4 signaling in progenitor expansion in bleomycin-induced lung injury. Methods Activation of the Bromodomain-containing protein 4 (BRD4) epigenetic regulator in distinct stem cell populations was quantitated in a high-resolution scRNA-seq time course of bleomycin-induced injury, and confirmed in scRNA-seq studies in human IPF. A potent, selective, and orally bioavailable BRD4 inhibitor (BRD4i, ZL0969) was rationally designed and synthesized. The effect of BRD4i on myofibroblast transition, progenitor cell expansion and fibrosis was evaluated using a therapeutic experimental design in C57BL6/mice. Results We find that the BRD4 pathway is rapidly induced in regenerating activated alveolar type (AT)2 cells and persists in a population of pro-fibrotic Krt8 + progenitors expressing markers of epithelial mesenchymal transition as well as senescence. To test the functional role of BRD4 activation, we administered a potent, selective, and orally bioavailable BRD4 inhibitor (BRD4i, ZL0969) with ~ 80 nM IC50 to bleomycin-treated mice. BRD4i reduced myofibroblast formation and deposition of denatured ECM (collagen and laminin a1) in the alveolar space and improved disease scores. Importantly, BRD4i reduced a pathogenic population of alveolar progenitor cells expressing integrin (ITG)-A6/B4, tumor related protein 63 (Trp63) and keratin (Krt). In mice given an LD50 dose of bleomycin, BRD4 inhibition significantly improved their survival and reduced markers of disease. Conclusions These data demonstrate that inhibition of BRD4 signaling prevents expansion of myofibroblasts and expansion of a pathogenic epithelial progenitor population controlling alveolar atypia and fibrosis.